Fractional yield and phase separation of ladder-like interpolymer complexation between diblock copolymers. (21st November 2019) - Fu, Chao; Yang, Yingzi; Qiu, Feng; Shi, An-Chang
Abstract: We analyze the fractional yield and the phase separation of the ladder-like interpolymer complexation reaction between two diblock copolymers A1 A2 and B1 B2 forming a linear triblock copolymer A1 DB1, i.e., A 1 A 2 + B 1 B 2 ⇌ A 1 DB 1 . The study is carried out by using the self-consistent field theory coupled with the interpolymer-complexation model of the chemical reactions. The fractional yield of the complexation ( φ 3 / φ ), defined as the equilibrium volume fraction of the triblock copolymers, can be improved via several approaches including increasing the secondary bonding energy ε Z D and enhancing the solvent selectivity to the triblock copolymer A1 DB1 . The strong solvent selectivity and the chemical incompatible interaction between the diblock copolymers and the triblock copolymers make the homogenous phase unstable. The phase separated state D/S emerges between the sigle-stranded-diblock-dominated phase S and the duplex-triblock-dominated phase D. With the fixed length of the diblock copolymers, the length of the complex block D influences the subtle balance among several contributions to the free energy including the bonding energy, the conformational entropic loss due to complexation, the solvent selectivity, and the interaction between the polymers. Graphical abstract: Image 1 Highlights: Block copolymer complexation A1 A2 +B1 B2 ⇌ A1 DB1, ladder-like complex D as DNA. Reaction yield controlled by bonding energy, solvent property, polymer interaction. Phase separation between high-yield phase and low-yield phase. Stabilize homogeneous phases by employing complexation-inactive polymer blocks.